Silent interests and all-pay auctions - Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2005)
If firms compete in all-pay auctions with complete information, silent shareholdings introduce asymmetric externalities into the all-pay auction framework. If the strongest firm owns a large share in the second strongest firm, this may make the strongest firm abstain from bidding. As a consequence, equilibrium profits of both firms may increase, but the prize may be allocated less efficiently. The reverse ownership structure is also likely to increase the profits of the firms involved in the ownership relationship but without these negative efficiency effects.
Keywords: L11; D44; L41; 330; all-pay auctions; externalities; contests; silent minority shareholdings; ownership structure; Auktionstheorie; Wettbewerb; Stille Gesellschaft; Eigentümerstruktur; Wirtschaftliche Effizienz; Theorie